PREVALENCE OF LOW BACK PAIN AND URINARY INCONTINENCE IN POST PREGNANT WOMEN - Tamali Chakraborty,; Dr. Manoj Kumar Mathur,; Dr. Tapas Kumar Pal, (The Bioscan, 2021)
BACKGROUND AND PURPOSE: Pain between the costal margins and the inferior gluteal folds which sometime referred down to the leg and accompanied by painful limitation of the movement known as nonspecific low back pain. diagnosing this pain is not related to conditions such as fractures, spondylitis, direct trauma, or neoplastic, infectious, vascular, metabolic, or endocrine–related processes. Another most common complication during pregnancy or after pregnancy is developing stress urinary incontinence (SUI).it has detrimental effects on the quality of life and SUI is an important social and hygienic health problem affecting adult women. People who develop SUI develops during pregnancy and after pregnancy without remission 3months after delivery have a very high risk of symptoms persistence 5years later. so, the objectives of this study are to determine the prevalence of LBP, pain referred down to the leg (LP), PGP, and stress urinary incontinence (SUI) and find the co-relation among them during post pregnancy phase in a large representative sample of pregnant INDIAN women. METHODS: This is a cross-sectional survey study where all the subjects were interviewed using Oswerty Low back pain questioner after taking their inform consent. Participants were selected conveniently from different areas of Kolkata. Women within age group of 25 to 40 who had a history of Low back pain after their Pregnancy will be included in this study. Pain without any history of Disc herniation was included in this study. History of Injury, Trauma, any other pathological conditions were excluded from this study. All participants of this study were given university approved informed consent. In addition, Research process will be explained in full. Research will start only after receipt of a signed informed consent. OUTCOMES MEASURES: Once all the participants were included in the study was assessed using The Questionnaire for The Revised Urinary Incontinence Scale (RUIS). RUIS is a scale which mainly consists of five QUESTION. RESULTS: In this study among 106 female participants 70 participants (66.03%) showed minimal disability, 21 participants (19.81%) showed moderate disability, 9 participants (8.49%) showed severe disability, 3 participants (2.83%) with bed bound condition due to back pain and disability with 3 participants (2.83%) needs serious medical Intervention. In this study among 106 participants 30 female participants were having mild symptoms (28.30%), 73 participants were having moderate symptoms (68.86%) and 3 participants were having severe symptoms (2.83%) as assessed by RUIS scale. CONCLUSION: This study concludes that post pregnant women are at higher risk of developing back pain which can vary minimal to moderate severity. Also, there is a mild to moderate risk of developing urinary incontinence among them. It’s the high time to find the probable cause for the same and positive interventions needed to prevent further complications. Prevalence of LBP is quite higher among women in comparison with men and post pregnancy the risk factor increases. Urinary incontinence also a predisposing factor after pregnancy and also a health hazards among women in older age groups. So positive interventions needed to solve these issues.